Temporal variability of surface air pollutants in megacities of South Korea - Lee, Taegyung; Go, Sujung; Lee, Yun Gon; Park, Sang Seo; Park, Jinsoo; Koo, Ja-Ho (Frontiers in Environmental Science, 2022)
This study investigated the various temporal (weekly, monthly, and inter-annual) variability of air pollutants (PM10, SO2, NO2, O3, CO) in seven megacities in South Korea (Seoul, Busan, Incheon, Daegu, Gwangju, Daejeon, and Ulsan). We found that the general decreasing trend of urban air pollutants except O3, which shows a clear increasing trend consistently in all seven megacities. Seasonally PM10, SO2, NO2, and CO have the highest level in winter due to the large fossil-fuel combustion for the heating demand, but O3 shows the maximum peak in summer induced by the intensified photochemistry. Based on the analysis for percentile values of air pollutants, we recognized some overlooked patterns of air pollutants in Korean megacities: O3 increase not perfectly related to the NO2 pattern, somewhat high SO2 in the coastal cities, ambiguous weekly pattern on Monday (as a weekday) and Sunday (as a weekend). Through this comprehensive analysis of multiple air pollutants using the percentile values, the characteristic for various temporal change of air pollutants in Korean megacities can be better understood, and some useful ideas for the air quality control in the urban region can be also excavated.